Komunikasi Dakwah Simbolik sebagai Upaya Pencegahan Aksi Kriminalitas Pelaku Pembegalan di Provinsi Bengkulu - Sopiyan, Wawan; Wardani, Rama Wijaya Kesuma (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2023)
This research aims to investigate the role of symbolic communication in robbery, with a focus on its relationship with drug use on the Lubuklinggau - Rejang Lebong border crossing, Bengkulu Province. The research method used was qualitative research with a case study approach involving interviews and field observations to collect comprehensive data about the motivation, intentions and communication strategies of the perpetrators. The research results reveal that symbolic communication plays a central role in planning and carrying out acts of robbery. Perpetrators use hand signals, certain codes, and body language as effective communication tools to achieve their goals. The perpetrators' primary motivation was related to material gain, with many of them admitting to robbery as a way to fund drug use. Additionally, drug use influences an offender's intent and contributes to complex crime cycles. The implications of this research for preventing and dealing with burglary are important. Prevention should include drug education programs, training of security personnel in detecting symbolic communications, and drug addiction prevention efforts. Additionally, rehabilitation and support for drug-related offenders should be an integral part of prevention strategies. Collaboration between multiple agencies, from law enforcement to mental health service providers, is key to addressing this complex issue.